2020
DOI: 10.3390/w12102770
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Prediction of Groundwater Hardness Using Ensemble Machine Learning Models

Abstract: Groundwater resources, unlike surface water, are more vulnerable to disturbances and contaminations, as they take a very long time and significant cost to recover. So, predictive modeling and prevention strategies can empower policymakers for efficient groundwater governance through informed decisions and recommendations. Due to the importance of groundwater quality modeling, the hardness susceptibility mapping using machine learning (ML) models has not been explored. For the first time, the current research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…Random forest (RF) is one of the machine learning models that has been considered in environmental modeling in recent years owing to its simplicity, robustness, and capacity to deal with complex data 21 . According to the authors’ knowledge, although the RF model has not been implemented to assess areas susceptible to asthma, its good performance has been proved in other environmental fields, such as groundwater potential 33 , groundwater hardness 22 , flood risk 23 , and PM 10 risk 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Random forest (RF) is one of the machine learning models that has been considered in environmental modeling in recent years owing to its simplicity, robustness, and capacity to deal with complex data 21 . According to the authors’ knowledge, although the RF model has not been implemented to assess areas susceptible to asthma, its good performance has been proved in other environmental fields, such as groundwater potential 33 , groundwater hardness 22 , flood risk 23 , and PM 10 risk 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Ensemble models, in particular, frequently outperformed single models [122]. For groundwater potential mapping, Mosavi et al [123] assessed four ensemble models, i.e., Boosted generalized additive model (GamBoost), adaptive Boosting classification trees (AdaBoost), Bagged classification and regression trees (Bagged CART), and random forest (RF), and found that the Bagging models (i.e., RF and Bagged CART) had a higher performance than the Boosting models (i.e., AdaBoost and GamBoost). This indicates that ensemble models outperformed other traditional ensemble models.…”
Section: Discussionmentioning
confidence: 99%
“…The RNNs performed best when time-lagged memory terms are built into the model for predictions. Mosavi [17] compared the performance of two ensemble decision tree models-boosted regression trees (BRT) and random forest (RF) to predict hardness of groundwater quality. More recently, Naloufi [18] used six machine learning (ML) models, including Decision Trees, to predict E. Coli concentrations in Marne River in France.…”
Section: Introductionmentioning
confidence: 99%